PENGARUH PELATIHAN, KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA KARYAWAN LAZ PERSADA JATIM - Winarno, Mochammad Agus (Prodi Magister Manajemen Universitas Wijaya Putra, 2023)
The purposes of this study are (1) to describe training, leadership, motivation, job satisfaction and employee performance at LAZ Persada Jatim, (2) to test and analyze the effect of training on employee job satisfaction at LAZ Persada Jatim, (3) to test and analyze the effect leadership on job satisfaction of LAZ Persada Jatim employees The results showed that training had a negative and insignificant effect on employee job satisfaction at LAZ Persada Jatim. Leadership had a positive and insignificant effect on employee job satisfaction, work motivation had a positive and insignificant effect on employee job satisfaction, training had a negative and insignificant effect on performance employees, leadership has a negative and insignificant effect on employee performance, work motivation has a positive and significant effect on employee performance, job satisfaction mediates positively and not significantly on the relationship between training and employee performance, job satisfaction is able to mediate positively and not significantly on the relationship between work motivation and employee performance, job satisfaction is able to mediate positively and not significantly on the relationship between leadership and employee performance, job satisfaction has a positive and significant effect on ki employee performance.